Klasifikasi Nilai Ujian Menggunakan Algoritma C5.0 di SMA Hangtuah 2 Sidoarjo - Pratiwi, Nisa; Anggraeny, Fetty Tri; Swari, Made Hanindia Prami (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2025)
Hangtuah 2 Sidoarjo High School is one of the educational institutions that implements intensive data management practices in all its operational activities. These activities start from processing student personal data, teacher lesson schedules, teaching management, attendance management, library management, financial management as well as evaluating and reporting student grades. In the evaluation process, teachers at Hangtuah 2 Sidoarjo High School often make mistakes in filling in the value data because there is too much data, so that the management of student grades becomes slow and calculation errors occur, resulting in ineffective classification of student grades. For this reason, this research aims to design an academic management system and test score classification using the C5.0 algorithm. With this system, it will be easier for administrators, teachers, librarians and finance departments to store student data and see their grades directly through the system. The results of the average percentage of all the questions that have been distributed have concluded that the UAT test results from the academic management system have very good criteria. The system that has been built can help teachers at Hangtuah 2 Sidoarjo High School to classify exam results based on the parameters of tuition arrears, number of books borrowed. , absenteeism, average UTS and UAS scores, accuracy results obtained from data from 37 students, test data, namely 70%..